LAYANAN INFORMASI TENTANG AKHLAK DALAM PENDIDIKAN ISLAM PESERTA DIDIK KELAS XI SMA ISLAM AL-ASYâ€™ARIYYAH - M, Mustakim; Asrori, M; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to describe information services about moral in Islamic education on grade XI Al-Asy'ariyyah Islamic High School Pontianak. The research method is descriptive in the form of a survey study. Population research as many as 28 students. The data collection technique used is indirect communication with a data collection tool in the form of a questionnaire. The data analysis technique is percentage. Overall, the implementation of information services on morals in Islamic education reached 82% including the good category. This means that the supervisor conducts information services about morals in Islamic education according to the theory. The material that has been conveyed about morals in education by counselors reaches 84% including good categories. The method that has been given by the guidance teacher in providing information services about morality in Islam reaches 80% including the good category. The media used by guidance teachers in providing information services about moral in Islam reached 79% including good categories.Â Keywords :Information Service, Moral in Islamic Education